Integrating Primary Care into the Management of Cystic Fibrosis - Roger Auth; Stephanie Catanese; Debasree Banerjee (SAGE Publishing, 2023)
Over the last 50 years, cystic fibrosis has radically transformed from a fatal disease of infancy to a chronic disease of adulthood. By 2025 it is estimated that 70% of individuals with cystic fibrosis (iwCF) will be cared for in adult clinics. We believe the role of a dedicated primary care provider (PCP) for preventative care will be crucial for the longevity of iwCF. There are various models for incorporating primary care medicine into CF management, but no universally accepted standard exists. Ideally, the PCP and pulmonologist practice in a patientcentered medical home, given the growing evidence that these care models are associated with improved quality-of-life measures, mental health, and disease-specific outcomes. To improve engagement with primary care in CF, there needs to be a shift in education at the undergraduate medical education and provider training levels. Increasing the knowledge of CF-related illness is vital in fostering a close relationship between the PCP and their patient. To meet this need, primary care doctors will need tools and practical experiences in managing this rare condition. This can start being addressed by providing ample opportunities for the inclusion of PCPs into subspecialty clinics and through engagement with community providers through readily available didactics, seminars, and open lines of communication. As PCPs and CF clinicians, we feel that shifting the domain of preventative care to the expertise of a primary care physician will allow for a more CF-specific focus in subspecialty clinics and help prevent these vital health maintenance tasks from being overlooked, altogether advancing the health and well-being of iwCF.